Pintu Otomatis Dengan Sensor Suhu Mlx90614 Berbasis Nodemcu Dan Telegram - Mudrika (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
Technological progress is something that cannot be avoided in this life, because technological progress will run in accordance with scientific advances. Every innovation is created to provide positive benefits for human life. One of the current uses of technology is to make it easier to check the human body temperature and the data is sent as quickly as possible via the internet. By assembling several electronic components, namely the HC-SR04 ultrasonic sensor and the MLX90614 temperature sensor as input, the NodeMCU microcontroller for the process and several output components, a tool will be made to support early detection of a process or prevent the transmission of a disease that is currently contagious, namely covid 19.